1983
DOI: 10.1017/s0317167100044577
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of Neurosarcoidosis and Clinicopathologic Correlation

Abstract: SUMMARY:In a retrospective study of 4,294 consecutive postmortem cases, there were 15 with histologically proved sarcoidosis, including 4 with CNS involvement. Whereas in previously reported autopsy series the prevalence of neurosarcoidosis was 15%, it is 27% in this review. Five cases with incidental, clinically inapparent sarcoidosis died at a mean age of 54.6 years; those six with systemic sarcoidosis, not involving the CNS, died at a mean age of 47.0 years; while those four with a variety of neurologic man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Although the prevalence is said to be 10-50 in 100,000 depending on the ethnical background, the disease might well be underdiagnosed as a post mortem study with an estimated prevalence of more than 600 in 100,000 suggests [1,2]. The nervous system is involved in 5-27% of cases with a broad range of symptoms including headache, aseptic meningitis, visual disturbances, cranial nerve palsy, spinal cord symptoms, brainstem or cerebellar signs and pituitary gland dysfunction [3][4][5][6][7]. However, the diagnosis of neurosarcoidosis remains difficult, especially in the absence of an established diagnosis of systemic sarcoidosis, which is the case in almost half of the patients with NS [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence is said to be 10-50 in 100,000 depending on the ethnical background, the disease might well be underdiagnosed as a post mortem study with an estimated prevalence of more than 600 in 100,000 suggests [1,2]. The nervous system is involved in 5-27% of cases with a broad range of symptoms including headache, aseptic meningitis, visual disturbances, cranial nerve palsy, spinal cord symptoms, brainstem or cerebellar signs and pituitary gland dysfunction [3][4][5][6][7]. However, the diagnosis of neurosarcoidosis remains difficult, especially in the absence of an established diagnosis of systemic sarcoidosis, which is the case in almost half of the patients with NS [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…32 33 are likely to be an unrelated late complication. 23 Acid fast coccobacillary bacteria have been identified in tissue…”
Section: Evidence For An Infective/transmissible Agentmentioning
confidence: 99%
“…5 The reported incidence of neurosarcoidosis (NS) is about 5% in patients with systemic sarcoidosis, 6,7 although postmortem studies have shown that the prevalence of the disease may be higher. 8 An incidence of 37% of central nervous system involvement has been reported in sarcoidosis when intraocular involvement is present. 9 In these cases, other causes of retinal phlebitis, such as multiple sclerosis (MS) or Behçet disease, need to be excluded.…”
mentioning
confidence: 99%